Auditoría ambiental y su impacto en el desarrollo económico en la empresa CERVECERÍA MISHKIARTESANAL S.A.S de la provincia del Cañar, cantón El Tambo, periodo enero a diciembre del 2022 - Agualongo Chimbo, Edgar Efrain (2023)
The environmental audit allows to evaluate the different operating procedures of a company, in order to identify the possible risks that contaminate the environment. Despite the importance of executing this mechanism, a large part of the organizations shows significant reluctance towards it, a situation linked to ignorance, execution costs and lack of knowledge about the different benefits. Objective: Carry out an environmental audit in the company called CERVECERÍA MISHKI ARTESANAL S.A.S., in the province of Cañar, canton of El Tambo, from January to December 2022. Methodology: Bibliographic and field research, with a mixed approach, addressed at a descriptive level, making use of the deductive, inductive, analytical and statistical methods. The population addressed were 5 workers and 1 manager, to whom a survey and an interview were applied. Results: The company CERVECERIA MISHKIARTESANAL S.A.S., presents a confidence level of 77.14 % (high) and an inherent risk level of 22.86% (low); In addition, it does not have an environmental management plan, a fundamental instrument to identify, record, and provide due follow-up to the possible environmental risks generated by the different procedures that are part of the company's operations. Conclusions: The environmental audit had an impact on the economic development during the period January - December 2022 of the company CERVECERIA MISHKI ARTESANAL S.A.S. Keywords: Environmental audit; economic development; Environmental risks; environmental management; environmental pollution.